Micronutrients intake during pregnancy and lactation - Mejia-Montilla, Jorly (2021)
Adequate nutritional status of women before, during and after pregnancy is essential to avoid both obstetric and perinatal complications. Micronutrients are essential for maternal and fetal development. Pregnancy has a special metabolic demand for high quality nutrients. In addition, adequate intake of vitamins, minerals and micronutrients can directly improve the quality of breast milk. Supplements can meet the increased demand for these elements during pregnancy and lactation, reducing the risk of fetal congenital anomalies, obstetric pathologies and development of chronic diseases in adulthood. However, there is conflicting information on the efficacy and safety of nutritional supplements during pregnancy. It is important that medical personnel can provide accurate and appropriate evidence-based advice on supplementation during pregnancy, as not all pregnant women need to use supplements on a regular basis, but it is necessary to identify pregnant women at risk of deficiency. The objective of this review was to analyze the effects of micronutrient intake in pregnancy and lactation.